The history of the state border of Kazakhstan and Uzbekistan.Қазақстан мен Өзбекстан арасындағы мемлекеттік шекараның пайда болу тарихы. (Journal of Oriental Studies, 2016)
The history of the administrative-territorial border between Kazakhstan and Uzbekistan starts with the formation of the Soviet state, and the specific designation of the border for the first time was recorded in the years 1924-1925 in the implementation of the national demarcation of the Central Asian republics. We are talking about the description of the boundaries between the RSFSR and the Uzbek Soviet Socialist Republic, as Kazakhstan at the time was part of the RSFSR. Description of the border was set out in the Annex to paragraph 9 of the Protocol №28 meeting of the Presidium of the All-Russian Central Executive Committee (Central Executive Committee) of the RSFSR of November 9, 1925 and executed by the military topographic maps structures created before the October Revolution, the royal period.Қазақстан мен Өзбекстанның арасында шекараға байланысты дау жоқ. Өйткені, екі мемлекет бір-бірінің аумағын белгілеп алған. Алайда, екі көршілес әрі туысқан халықтардың мемлекеттік шекарасы қалай пайда болды, оның сызылуына қатысты белгілі бір кедергілер туды ма дегенсұрақтар төңірегінде деректер жиналған. Қазақстан жағы Өзбекстанғақоятын белгілі бір территориялық даулардың баяғыда бар болғандығыда айтылады. Алайда,Мәскеудің солақай саясаты көптеген шешімдергеараласып, екі елдің арасында белгілі бір салқындық тигізді деугетолық негіз бар.